Hubungan Antara Regulasi Emosi Dengan Penerimaan Kelompok Teman Sebaya pada Siswa di SMAN 7 Kupang - Wonga, Maria Yasintha; Lohmay, Imanuel; Korohama, Katharina E.P; Nalle, Andriani P (Prodi Bimbingan Konseling FKIP UNDANA, 2024)
This research aims to determine 1) a description of students' emotional regulation 2) a description of peer group acceptance and 3) analyze the relationship between emotional regulation and peer group acceptance among students at SMA Negeri 7 Kupang. This research uses a quantitative approach with descriptive correlation research. The total sample involved in this research was 84 students taken using random sampling techniques. Data collection techniques used the Emotion Regulation Scale and Peer Group Acceptance Questionnaire developed by the researcher. The data analysis technique used is descriptive analysis and correlation analysis with the SPSS application. The research results showed that as many as 43% (36 students) were in the low category for emotional regulation abilities. Furthermore, peer group acceptance is also in the low category with a percentage of 38% (32 students). The results of product moment correlation analysis show that emotional regulation has a significant relationship with peer group acceptance at a significance level of 0.05. Furthermore, it is known that relationships are positive so that the higher the emotional regulation, the higher the acceptance of the peer group. These findings recommend the importance of improving emotion regulation skills at the secondary school level in the context of peer group acceptance.